Impact of coagulation as a pre-treatment for UVC/H2O2-biological activated carbon treatment of a municipal wastewater reverse osmosis concentrate. (1st January 2016) - Umar, Muhammad; Roddick, Felicity; Fan, Linhua
Abstract: After coagulation of high salinity reverse osmosis concentrate (ROC) with either alum or ferric chloride followed by UVC/H2 O2 treatment, biological activated carbon (BAC) was investigated for the removal of DOC. BAC treatment mainly removed low molecular weight (LMW) neutral molecules indicating that biodegradation was the predominant mechanism of organic matter removal. Coagulation with ferric chloride gave greater DOC reductions than alum both as a stand-alone treatment and after the sequence of UVC/H2 O2 and BAC treatment. However, overall reduction after the sequence of coagulation, UVC/H2 O2 and BAC treatment was only marginally greater for ferric chloride (68%) than for alum (62%). Trihalomethane formation potential and N-Nitrosodimethylamine concentration decreased markedly after UVC/H2 O2 treatment. UVC/H2 O2 treatment of the ROC led to the generation of extreme toxicity according to the Microtox assay, but no toxicity was observed after BAC, demonstrating its advantage for enabling safe disposal of the treated ROC. Implementation of coagulation as a pre-treatment and BAC as a post-treatment markedly reduced (6–8 times) the electrical energy dose ( E ED) required for the UVC/H2 O2 process. The sequence of coagulation, UVC/H2 O2 and BAC treatment was demonstrated as a potential process for the removal of organic matter from high salinity municipal ROC. Graphical abstract: Highlights: Coagulation + UV/H2 O2 + BAC treatment removed DOC from reverse osmosis concentrate. Coagulation with ferric chloride gave greater DOC removal than with alum. Decreased THMFP, NDMA and ecotoxicity levels were obtained after the treatment. Ferric chloride coagulation plus BAC treatment is a possible option.